How Metabolic State May Regulate Fear: Presence of Metabolic Receptors in the Fear Circuitry - Koorneef, Lisa L.; Bogaards, Marit; Reinders, Marcel J. T.; Meijer, Onno C.; Mahfouz, Ahmed (Frontiers in Neuroscience, 2018)
Metabolic status impacts on the emotional brain to induce behaviour that maintains energy balance. While hunger suppresses the fear circuitry to promote explorative food-seeking behaviour, satiety or obesity may increase fear to prevent unnecessary risk-taking. Here we aimed to unravel which metabolic factors, that transfer information about the acute and the chronic metabolic status, are of primary importance to regulate fear, and to identify their sites of action within fear-related brain regions. We performed a de novo analysis of central and peripheral metabolic factors that can penetrate the blood-brain barrier using genome-wide expression data across the mouse brain from the Allen Brain Atlas (ABA). The central fear circuitry, as defined by subnuclei of the amygdala, the afferent hippocampus, the medial prefrontal cortex and the efferent periaqueductal gray, was enriched with metabolic receptors. Some of their corresponding ligands were known to modulate fear (e.g. estrogen and thyroid hormones) while others had not been associated with fear before (e.g., glucagon, ACTH). Additionally, several of these enriched metabolic receptors were coexpressed with well-described fear-modulating genes (Crh, Crhr1 or Crhr2). Co-expression analysis of monoamine markers and metabolic receptors suggested that monoaminergic nuclei have differential sensitivity to metabolic alterations. Serotonergic neurons expressed a large number of metabolic receptors (e.g. estrogen receptors, fatty acid receptors), suggesting a wide responsivity to metabolic changes. The noradrenergic system seemed to be specifically sensitive to hypocretin/orexin modulation. Taken together, we identified a number of novel metabolic factors (glucagon, ACTH) that have the potential to modulate the fear response. We additionally propose novel cerebral targets for metabolic factors (e.g. thyroid hormones) that modulate fear, but of which the sites of action are (largely) unknown.